Integrated climate modelling at the Kiel Institute for World Economics: The DART Model and its applications - Oliver Deke; Sonja Peterson (Institut für Weltwirtschaft (IfW), 2003)
The aim of this paper is to give an overview over the DART model and its applications. The main focus is on the implementation of climate impacts into DART in the course of coupling DART to the ocean-atmosphere model and on the associated empirical problems. The basic DART model and some applications are presented in the next section. Section 3 describes in detail how the economic impacts of climate change on the agricultural sector and the impact of sea level rise are implemented in DART. Section 4 presents selected simulation results. Section 5 concludes.
Conference: 1st International Workshop on "Integrated Climate Models: An interdisciplinary assessment of climate impacts and policies", October 2nd - 3rd, 2003, ITCP Trieste, Italy
Keywords: 330; Klimaveränderung; Klimaschutz; Allgemeines Gleichgewicht; Mehr-Länder-Modell; Mehr-Sektoren-Modell; Theorie